Circuits for differential signal extraction in the lock–in amplifiers; IOP Conference Series: Materials Science and Engineering; Vol. 66: 20th International Conference for Students and Young Scientists: Modern Techniques and Technologies (MTT'2014), Tomsk, Russia, 14-18 April 2014 - Baranov P. Pavel (2014, 2014)
Title screen